2017
DOI: 10.1016/j.ajog.2016.12.173
|View full text |Cite
|
Sign up to set email alerts
|

Are perioperative bundles associated with reduced postoperative morbidity in women undergoing benign hysterectomy? Retrospective cohort analysis of 16,286 cases in Michigan

Abstract: Background Healthcare teams that frequently follow a bundle of evidence-based processes provide care with lower rates of morbidity. Few process bundles to improve surgical outcomes in hysterectomy have been identified. Objectives To investigate if a bundle of four perioperative care processes is associated with fewer postoperative complications and readmissions for hysterectomies in the Michigan Surgical Quality Collaborative (MSQC). Study Design A bundle of perioperative care process goals was developed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…The study demonstrated statistically significant postoperative complications where HA was used including: increased rate of blood transfusions, increased rate of pelvic abscess diagnosis, increased hospital readmission, and increased predicted rate of reoperation. 40 Postoperative complications were limited amongst the included articles. In our systematic review of the literature, no statistically significant postoperative complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated statistically significant postoperative complications where HA was used including: increased rate of blood transfusions, increased rate of pelvic abscess diagnosis, increased hospital readmission, and increased predicted rate of reoperation. 40 Postoperative complications were limited amongst the included articles. In our systematic review of the literature, no statistically significant postoperative complications were reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the gynecologic literature, there are only a few studies evaluating the efficacy of SSI reduction bundling [8, 32]. The most noteworthy data were reported in a 2016 publication by Johnson and colleagues from the Mayo Clinic [8].…”
Section: Discussionmentioning
confidence: 99%
“…2,17 Moreover, compliance with each additional bundle element leads to step-wise decreases in infection and complication rates. 5,18 Another possible limitation in the study was the identification used. [19][20][21][22] Notably, SSI rates from the NHSN tend to be lower than those from other sources.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible to determine the contribution of each bundle element in preventing infections, previous data suggest that the use of any bundle promotes adherence to best practices and thus improves infection rates 2,17 . Moreover, compliance with each additional bundle element leads to step‐wise decreases in infection and complication rates 5,18 …”
Section: Discussionmentioning
confidence: 99%